Nanoconfinement of magnesium hydride in porous scaffolds for hydrogen storage: Kinetics, thermodynamics, and future prospects - Saeid, Mohammed Faraj; Abdulkadir, B. A.; Sumaiya, Zainal Abidin; Herma Dina, Setiabudi (Elsevier Ltd, 2025)
Hydrogen shows great promise as a versatile energy carrier for various clean energy applications; however, it remains challenging to develop an efficient and safe storage system. Hydrogen must be stored in chemical materials like ammonia borane (NH3BH3) and sodium borohydride (NaBH4) or metal hydride materials for proper use. Among the frequently reported hydrides, magnesium hydride (MgH2) gained significant consideration as a highly prospective material for energy storage applications. Nevertheless, the hands-on use of MgH2 is restricted by its high thermodynamic barriers and slow kinetics. Therefore, nanoconfinement of MgH2 in porous materials has appeared as a promising strategy to enhance its kinetics and thermodynamic performance. This review paper summarizes the present research on how nanoconfinement influences the kinetics and thermodynamics of MgH2 during the hydrogen adsorption/desorption process within different porous scaffolds. The review also highlights the challenges associated with the nanoconfinement approach, including the need for a fundamental understanding of the nanoconfinement effects and the development of materials with enhanced stability and cycling performance. Finally, future research directions that could lead to high storage capacity at ambient conditions based on nanoconfined MgH2 were explained. Based on the study findings, the most promising scaffolds are carbon-based materials due to their high surface area, tunable pore structures, lightweight nature, and excellent thermal and chemical stability. Hopefully, this article will serve as an eye-opening point for prospective studies in hydrogen storage using MgH2 through confinement in porous scaffolds.